⎩ ⎪ ⎪ ⎨ ⎪ ⎪ ⎧ f ( 1 7 2 9 ) = 4 f ( 1 7 3 0 ) = 5 f ( 1 7 3 1 ) = 6
Let f ( x ) be a cubic polynomial satisfying the following system of equations. Find ∫ 1 7 2 9 1 7 3 1 f ( x ) d x .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
We can use Simpson's rule , which gives the exact value of the integral for polynomials of degree ≤ 3 . Therefore,
∫ 1 7 2 9 1 7 3 1 f ( x ) d x = 6 1 7 3 1 − 1 7 2 9 [ f ( 1 7 3 1 ) + 4 f ( 2 1 7 3 1 + 1 7 2 9 ) + f ( 1 7 2 9 ) ] = 1 0
Problem Loading...
Note Loading...
Set Loading...
It is easy to identify: f ( x ) = A ( x − 1 7 2 9 ) ( x − 1 7 3 0 ) ( x − 1 7 3 1 ) + x − 1 7 2 5 (See Polynomial Interpolation )
Hence, ∫ 1 7 2 9 1 7 3 1 f ( x ) d x = ∫ 1 7 2 9 1 7 3 1 ( A ( x − 1 7 2 9 ) ( x − 1 7 3 0 ) ( x − 1 7 3 1 ) + x − 1 7 2 5 ) d x Substituting x-1730=t such that dx=dt = ∫ − 1 1 ( A ( t + 1 ) ( t ) ( t − 1 ) + t + 5 ) d t = ∫ − 1 1 ( A t 3 − A t + t + 5 ) d t = 0 + 1 0 = 1 0
∗ ∗ ∫ − 1 1 ( A t 3 − A t + t ) d t = 0
since A t 3 − A t + t is a odd function by using- if f ( x ) is an odd function, then ∫ − a a f ( x ) d x = 0 .